If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-2x + 7) = 66 Reorder the terms: 6(7 + -2x) = 66 (7 * 6 + -2x * 6) = 66 (42 + -12x) = 66 Solving 42 + -12x = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -12x = 66 + -42 Combine like terms: 42 + -42 = 0 0 + -12x = 66 + -42 -12x = 66 + -42 Combine like terms: 66 + -42 = 24 -12x = 24 Divide each side by '-12'. x = -2 Simplifying x = -2
| 2m=-3m+-3 | | 7x+9+2x=6x-18 | | 3=2j-7 | | 5y+5=7y-7 | | -4x+3=21 | | 3(x-1)+2x=7 | | 4v+8=44 | | W-11=11 | | 12+5x=1+4x+3 | | -4+3=21 | | -2(-9+6x)=-18 | | -2y+24=30 | | 18=8+2h | | 31=3u+10 | | 5x^2+18x+-8=0 | | -133+10x=-7x+91 | | 23-c=21 | | -7x+8=-6x+9 | | -84=-7(p-2)-7p | | 49a^2-70a+25=0 | | -7x+4=22-4x | | 3(9+2x)=21 | | 7x+9-4x=15 | | y+9=6-2y | | 35-x-24= | | 3x-2+4-x=-4 | | 4d+3= | | 5m-2m-2=m-10 | | 6n-4=3n+11 | | 4x^2=-9+12x | | 2x-5=x+7-3x | | 6x+80+18x-40=180 |